The combination of diethyldithiocarbamate and copper ions is active against Staphylococcus aureus and Staphylococcus epidermidis biofilms in vitro and in vivo - Kaul, Laurine; Abdo, Adrian I.; Coenye, Tom; Krom, Bastiaan P.; Hoogenkamp, Michel A.; Zannettino, Andrew C. W.; Süss, Regine; Richter, Katharina (Frontiers in Microbiology, 2022)
Staphylococcus aureus and Staphylococcus epidermidis are associated with life-threatening infections. Despite the best medical care, these infections frequently occur due to antibiotic resistance and the formation of biofilms of these two bacteria (i.e., clusters of bacteria embedded in a matrix). As a consequence, there is an urgent need for effective anti-biofilm treatments. Here, we describe the antibacterial properties of a combination treatment of diethyldithiocarbamate (DDC) and copper ions (Cu2+) and their low toxicity in vitro and in vivo. The antibacterial activity of DDC and Cu2+ was assessed in vitro against both planktonic and biofilm cultures of S. aureus and S. epidermidis using viability assays, microscopy, and attachment assays. Cytotoxicity of DDC and Cu2+ (DDC-Cu2+) was determined using a human fibroblast cell line. In vivo antimicrobial activity and toxicity were monitored in Galleria mellonella larvae. DDC-Cu2+ concentrations of 8 µg/ml DDC and 32 µg/ml Cu2+ resulted in over 80% MRSA and S. epidermidis biofilm killing, showed synergistic and additive effects in both planktonic and biofilm cultures of S. aureus and S. epidermidis, and synergized multiple antibiotics. DDC-Cu2+ inhibited MRSA and S. epidermidis attachment and biofilm formation in the xCELLigence and Bioflux systems. In vitro and in vivo toxicity of DDC, Cu2+ and DDC-Cu2+ resulted in >70% fibroblast viability and >90% G. mellonella survival. Treatment with DDC-Cu2+ significantly increased the survival of infected larvae (87% survival of infected, treated larvae vs. 47% survival of infected, untreated larvae, p<0.001). Therefore, DDC-Cu2+ is a promising new antimicrobial with activity against planktonic and biofilm cultures of S. epidermidis and S. aureus and low cytotoxicity in vitro. This gives us high confidence to progress to mammalian animal studies, testing the antimicrobial efficacy and safety of DDC-Cu2+.